Total synthesis of elansolids B1 and B2 - Wang, Liang-Liang; Kirschning, Andreas (Beilstein Journal of Organic Chemistry, 2017)
The elansolids A1–A3, B1, and B2 are secondary metabolites formed by the gliding bacterium Chitinophaga sancti. They show antibacterial activity against Gram-positive bacteria. A second generation total synthesis of the antibiotic elansolid B1 (2) and the first synthesis of elansolid B2 (3) are reported. In contrast to previous work, the (Z,E,Z)-triene at C10–C15 was assembled by using an optimized C–C cross-coupling sequence with a Suzuki cross-coupling reaction as key step.
Keywords: antibiotics; polyenes; polyketides; Stille reaction; Suzuki reaction; total synthesis